2015
DOI: 10.1080/00071668.2015.1101053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aBacillusdirect-fed microbial candidate on digesta viscosity, bacterial translocation, microbiota composition and bone mineralisation in broiler chickens fed on a rye-based diet

Abstract: 1. The effects of the dietary inclusion of a Bacillus-based direct-fed microbial (DFM) candidate on digesta viscosity, bacterial translocation, microbiota composition and bone mineralisation were evaluated in broilers consuming rye-based diets. 2. In the present study, control mash rye-based diets (CON) or Bacillus-DFM supplemented diets (TRT) were administered ad libitum to male broilers in three independent experiments. 3. In Experiments 1 and 2 (n = 25/group), liver samples were taken to evaluate bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 43 publications
1
56
0
4
Order By: Relevance
“…Broilers fed Bacillus ‐supplemented diets exhibit reduced digesta viscosity caused by soluble nonstarch polysaccharide, which can affect nutrient availability and absorption (Latorre et al . ). In addition to promoting the growth performance and health of poultry, feed with added Bacillus also improves the quality of meat (e.g.…”
Section: Mode Of Action and Efficiency Of Bacillus In Terrestrial Andmentioning
confidence: 97%
See 1 more Smart Citation
“…Broilers fed Bacillus ‐supplemented diets exhibit reduced digesta viscosity caused by soluble nonstarch polysaccharide, which can affect nutrient availability and absorption (Latorre et al . ). In addition to promoting the growth performance and health of poultry, feed with added Bacillus also improves the quality of meat (e.g.…”
Section: Mode Of Action and Efficiency Of Bacillus In Terrestrial Andmentioning
confidence: 97%
“…Sen et al (2012) observed that administration of Bacillus causes histomorphological changes in the intestine of broilers, increasing villus height and villus height to crypt dept ratio, and thus improves the nutrient digestibility and absorption capacity of the small intestine. Broilers fed Bacillussupplemented diets exhibit reduced digesta viscosity caused by soluble nonstarch polysaccharide, which can affect nutrient availability and absorption (Latorre et al 2015). In addition to promoting the growth performance and health of poultry, feed with added Bacillus also improves the quality of meat (e.g.…”
Section: Poultrymentioning
confidence: 99%
“…Previous results from our laboratory have demonstrated that in poultry, chemically induced disruption of TJs with DSS (10) increases transmucosal permeability as seen by elevated serum levels of FITC-d (11). On the other hand, recently, we have shown that dietary inclusion of a Bacillus -based direct-fed microbial ameliorated the adverse gut permeability inflammatory effects related to utilization of rye-based diets in turkeys and in broiler chickens (15, 16). We have previously shown that FITC-d can be used as a biomarker for intestinal barrier function (712).…”
Section: Introductionmentioning
confidence: 98%
“…The increase of digesta transit induces higher bacteria proliferation, especially undesirable microbes such as Escherichia coli and Clostridium perfringens [46,47]. Moreover, diets with high NSP promote higher bacterial translocation from the gut to the blood system, due to the leaky gut [48,49] that can produce systemic infection and inflammation.…”
Section: Non-starch Polysaccharidesmentioning
confidence: 99%